Association of clinical parameters with periodontal bacterial haemolytic activity. (4th May 2016) - Wong, Benedicta K. J.; McGregor, Neil R.; Butt, Henry L.; Knight, Rachel; Liu, Louise Ye; Darby, Ivan B.
Abstract: Aims: To determine whether haemolytic activity of subgingival bacteria is associated with periodontitis clinical parameters and to identify which bacteria produce the haemolysins. Materials and Methods: Subgingival plaque samples from 22 untreated chronic periodontitis patients were investigated by culture and identified with matrix assisted laser desorption/ionisation time‐of‐flight mass spectrometry. Results: Total aerobic and anaerobic bacterial viable counts, percentage distribution of α ‐ and β ‐haemolytic bacteria were significantly elevated in diseased sites in relation to healthy sites ( p  <   0.001). Periodontal pathogens were more frequently detected at diseased sites: Porphyromonas gingivalis, Tannerella forsythia, Treponema sp., Prevotella sp., Parvimonas micra, Fusobacterium sp., Campylobacter sp., Capnocytophaga sp., and Selenomonas sp. Haemolytic unidentifiable species and Gram‐positive anaerobes such as Slackia exigua, Solobacterium moorei, and Bulledia extructa were also more frequently detected at diseased sites. In diseased sites, the presence of different haemolytic characteristics was more strongly correlated with clinical measures of disease than the mere absence or presence of specific species. The strongest correlation with probing pocket depth was observed for overall β ‐haemolytic toxicity ( r  =   0.73, p  <   0.001). Conclusion: A strong association was observed between subgingival bacterial haemolytic activity and clinical parameters in patients with chronic periodontitis. Further investigations are warranted to delineate the role of haemolysins in the pathogenesis of periodontitis.